2009
DOI: 10.1007/s00192-009-0930-x
|View full text |Cite
|
Sign up to set email alerts
|

Conservative versus surgical management of prolapse: what dictates patient choice?

Abstract: Nearly two thirds of women with symptomatic prolapse initially opted for conservative management. Women choosing surgery over pessaries for treatment of prolapse describe more severe symptoms related to bowel emptying, sexual function, and quality of life and are bothered by them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 23 publications
2
50
0
2
Order By: Relevance
“…In our study, there was a high prevalence of urinary, prolapse, and colorectal-anal symptoms in women presenting with POP, although the prevalence of all three was lower than reported in the literature [13,14]. As expected, SUI was more prevalent in the stage I/II POP group.…”
Section: Discussionsupporting
confidence: 57%
“…In our study, there was a high prevalence of urinary, prolapse, and colorectal-anal symptoms in women presenting with POP, although the prevalence of all three was lower than reported in the literature [13,14]. As expected, SUI was more prevalent in the stage I/II POP group.…”
Section: Discussionsupporting
confidence: 57%
“…The 1-year follow-up achieved in our study is better and certainly comparable with most prospective questionnaire follow-up studies [2][3][4][5][6]. This cannot be referred to as "selective loss to follow-up" but represents the real-life situation when women are treated with pessaries or surgery.…”
supporting
confidence: 83%
“…Compared to our results, we found a much higher percentage (43%, includes all patients). In the study of Kapoor et al [8], this percentage is even higher (approximately 65%). In contrast to our study, these studies were trying to find predictors for pessary use while we were showing the patients (dis)advantages.…”
Section: Discussionmentioning
confidence: 88%
“…However, previous studies have identified patient characteristics that are associated with successful pessary treatment. There is a strong association between age and continued pessary use [4,5,6,7,8]. Preference for surgery as well as the presence of a posterior compartment prolapse appears to be associated with an increased risk on discontinuation of a pessary [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation